Analysis and Characterisation of Interactions in Face-to-Face and Remote-Access Chemistry Laboratories - Wei, Jianye (Curtin University, 2019)
Laboratories have long been integral components in the undergraduate science curriculum. With the advancement of technologies, remote laboratories have been developed to complement or even replace some traditional face-to-face laboratories. This research investigated the process of learning in both face-to-face and remote laboratories by understanding interactions from the viewpoint of students, and their satisfaction levels. Findings from this research provide information for curriculum designers, laboratory instructors and students.